Improving Public Good Supply and Income Equality: Facing a Trade-Off - Wolfgang Buchholz; Dirk Rübbelke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
It is explored in this paper how – depending on the agents' preferences – an unequal income distribution may lead to a higher public good supply in a non-cooperative Nash equilibrium than in a cooperative Lindahl equilibrium that arises from a balanced income distribution. The degree of inequality that is needed for producing this result may be moderate what in particular is shown through an example with CES preferences.
Keywords: D31; H41; Q54; 330; public good; Nash equilibrium; Lindahl equilibrium; income distribution